Fabrication and Characterization of Single-Walled Carbon Nanotubes from La2O3 Nanoparticles by Ethanol Chemical Vapour Deposition - Wang, Chunyan; Shi, Jun; Le, Zhanggao (Asian Journal of Chemistry, 2012)
The lanthanum sesquioxide is an active and efficient catalyst for the growth of single-walled carbon nanotubes by a catalytic chemical vapour deposition process. Horizontally superlong well-oriented single-walled carbon nanotubes on SiO2/Si wafer surface can be fabricated via EtOH as carbon source when the temperature is in the range of 700-950 ºC. The carbon nanostructures are characterized by electronic microscopy, atomic force microscopy, Raman spectroscopy, X-ray diffraction, etc. As-grown single-walled carbon nanotubes from La2O3 have compatibly high quality and purity. This novel oxide provides a new experimental avenue to understand the growth mechanism of single-walled carbon nanotubes and a series of replaceable catalysts for nanotubes growth has been developed, which may be helpful for their controllable synthesis.